Welcome, Holy Spirit : how you can experience the dynamic work of the Holy Spirit in your life - Hinn, Benny (Nashville : Thomas Nelson, 1995)
How you can experience the dynamic work of the Holy Spirit in your life.
Includes bibliographical references (pages 272-277).
Keywords: Holy Spirit; Holy Spirit -- Biblical teaching; Christian life -- Pentecostal authors